CEU Graduation Ceremony 2002 - Part 2
Recording of CEU’s 11th Graduation Ceremony on June 20, 2002. The ceremony continues with the conferring of the master’s degrees. Participants: Yehuda Elkana (Rector and President of CEU), George Soros (Founder of CEU and Chairman of the Board of Trustees), the Heads of the Departments and the MA candidates.